PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SFE (STUDENT FACILIATOR AND EXPLAINING) DALAM MENINGKATKAN HASIL BELAJAR PAI PESERTA DIDIK - Susanti, Agus (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This research is motivated by the low learning outcomes of seventh-grade students in Islamic Religious Education (PAI) at SMP Negeri 16 Bandar Lampung, particularly in the topic of congregational and shortened prayers, where 63.49% of students fell below the Minimum Completion Minimum (KKM). This condition is thought to be due to the implementation of conventional, teacher-centered learning methods and a lack of student involvement. The focus of this study is to examine the effect of the Student Facilitator and Explainer (SFE) cooperative learning model on improving Islamic Religious Education (PAI) learning outcomes. This study used a quantitative method with a quasi-experimental design (pretest-posttest control group design). The sample consisted of two classes (VII D as the experimental class and VII F as the control class) selected purposively. Learning outcome data were collected through tests and analyzed using a t-test after passing validity, reliability, normality, and homogeneity tests. The results showed a significant difference in learning outcomes (Sig. 0.000 < 0.05). The posttest average for the experimental class (84.50) was significantly higher than that for the control class (65.00). It was concluded that the SFE model had a significant and effective effect on improving Islamic Religious Education learning outcomes by encouraging student involvement, responsibility, and better understanding of concepts. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar Pendidikan Agama Islam (PAI) siswa kelas VII SMP Negeri 16 Bandar Lampung, khususnya pada materi shalat jama’ dan qashar, di mana 63,49% siswa berada di bawah KKM. Kondisi ini diduga akibat penerapan metode pembelajaran konvensional yang berpusat pada guru dan kurangnya keterlibatan siswa. Fokus penelitian ini adalah untuk menguji pengaruh model pembelajaran kooperatif tipe Student Facilitator and Explaining (SFE) terhadap peningkatan hasil belajar PAI. Penelitian ini menggunakan metode kuantitatif dengan desain quasi-experiment (pretest-posttest control group design). Sampel terdiri dari dua kelas (VII D sebagai kelas eksperimen dan VII F sebagai kelas kontrol) yang dipilih secara purposive. Data hasil belajar dikumpulkan melalui tes, dianalisis menggunakan uji-t setelah lolos uji validitas, reliabilitas, normalitas, dan homogenitas. Hasil penelitian menunjukkan perbedaan signifikan pada hasil belajar (nilai Sig. 0,000 < 0,05). Rata-rata posttest kelas eksperimen (84,50) jauh lebih tinggi daripada kelas kontrol (65,00). Disimpulkan bahwa model SFE berpengaruh signifikan dan efektif dalam meningkatkan hasil belajar PAI dengan mendorong keterlibatan, tanggung jawab, dan pemahaman konsep siswa secara lebih baik.